2016
DOI: 10.1061/(asce)wr.1943-5452.0000686
|View full text |Cite
|
Sign up to set email alerts
|

Field Data–Based Methodology for Estimating the Expected Pipe Break Rates of Water Distribution Systems

Abstract: Presented in this paper is a field data-based probabilistic approach to quantifying the expected pipe break rates of water distribution systems. Uncertain demands and variations in the roughness of pipes during their service lives are described as random variables. Sample values of these random variables are generated and input to a distribution system model to determine the resulting minimum and maximum pressures in Monte Carlo simulations. Based on an estimated break rate-maximum pressure relationship, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ultimately, they found that results of LS-SVM was more accurate than those obtained by Feed Forward Neural Network (FFNN) and Generalized Regression Neural Network (GRNN) techniques. Ghorbanian et al (2016) proposed a probabilistic approach to assess pipes break rates occurred in a part of the City of Hamilton WDN in Ontario, Canada. The performance of the proposed technique results demonstrated that the frequency of low-pressure occurrences is significantly marginal whereas a higher minimum pressure criterion would unavoidably augment expected pipe break rates.…”
Section: Literature Review: Overview Of Existing Techniquesmentioning
confidence: 99%
“…Ultimately, they found that results of LS-SVM was more accurate than those obtained by Feed Forward Neural Network (FFNN) and Generalized Regression Neural Network (GRNN) techniques. Ghorbanian et al (2016) proposed a probabilistic approach to assess pipes break rates occurred in a part of the City of Hamilton WDN in Ontario, Canada. The performance of the proposed technique results demonstrated that the frequency of low-pressure occurrences is significantly marginal whereas a higher minimum pressure criterion would unavoidably augment expected pipe break rates.…”
Section: Literature Review: Overview Of Existing Techniquesmentioning
confidence: 99%
“…Burst frequency generally depends on the pipe age, pipe material, external load, and climate conditions. Different models are developed to investigate this dependency [13]. Lambert et al developed the following equation [55]:…”
Section: Burst Frequency Simulationmentioning
confidence: 99%
“…Using local field data, Ghorbanian et al [13] proposed a probabilistic approach that considers uncertain demands and pipe roughness to determine the effects of pressure on burst frequency. The Monte Carlo method was used to implement this probabilistic approach in the water network of Hamilton, Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%